Router remote monitoring using android application - Chong, Jian Dong (2014)
Router Monitoring using Android Application is a mobile application that provides the function to remotely viewing the router status by network administrator. In the networking environment, constantly monitor the router status will reduce unnecessary loss to one organization when network problem occur. The purpose of this development is to provide easy monitoring of the network router device for network administrator. With this application, network administrator can obtain real time network information at their fingertips from anywhere with prerequisite of internet connection. With full support of push notification, network administrator will know immediately when there are important updates such as interface down, helping you keep tab of all the devices from the palm of your hand. Therefore, network administrator can react to the network problem as soon as possible before it affects other network device. An advantage of this application is that network administrator will not miss any networks failures that occur at any time. This application has some limitation in term of information gathers, this application just report router status information of router such as interface status. There is still need improvement in order to increase the functionality of this application such as adding the performance report of the router.